Intervensi Pemenuhan Relatedness untuk Meningkatkan Kesejahteraan Psikologis Anggota Karang Taruna RW.004 Karet Semanggi - Pangkey, Wilfred Audric Clief; Djukardi, Timothi; Khumairoh, Fira; Tasdin, Willy (IAI Nasional Laa Roiba Bogor, 2025)
Background: Relatedness, or social connectedness, is a basic psychological need essential for mental well-being, especially during late adolescence to early adulthood. Observations of Karang Taruna RW.04 members in Karet Semanggi indicated that relatedness was the least fulfilled psychological aspect. This community service program aimed to enhance participants’ social connectedness. Method: A single-session intervention was conducted using an experiential learning approach, integrating Social Identity Mapping and psychoeducation on the importance of relatedness. Result: Pre- and post-test measurements showed an increase in relatedness scores across all participants. Conclusion: This activity proved effective in raising awareness of healthy social relationships and supporting the fulfillment of basic psychological needs for youth mental well-being.